Optimizing the production and processing of fibre reinforced thermoplastic pre-impregnated materials - Novo, P. J. (2014)
The aim of this work is to optimize the production of new continuous carbon fibres reinforced polypropylene matrix pre-impregnated materials (towpregs) continuously processed by dry deposition of polypropylene (PP) powder. The processing of the produced towpregs by pultrusion using a prototype equipment was also optimized. The method of Taguchi/DOE (Design of Experiments) was used to achieve this goal allowing improved choices of processing windows. Towpregs were characterized by scanning electron microscopy (SEM), visual analysis and their polymer mass contents were also determined. The final pultruded composite profiles were also submitted to tensile, interlaminar, flexural, calcination and optical microscopy tests.